NMD: RNA biology meets human genetic medicine - Bhuvanagiri, Madhuri; Schlitter, Anna Melissa; Hentze, Matthias W.; Kulozik, Andreas (Biochemical journal, 2010)
NMD (nonsense-mediated mRNA decay) belongs to the best-studied mRNA surveillance systems of the cell, limiting the synthesis of truncated and potentially harmful proteins on the one hand and playing an initially unexpected role in the regulation of global gene expression on the other hand. In the present review, we briefly discuss the factors involved in NMD, the different models proposed for the recognition of PTCs (premature termination codons), the diverse physiological roles of NMD, the involvement of this surveillance pathway in disease and the current strategies for medical treatment of PTC-related diseases.
Gesehen am 01.02.2023